VIDEOSCRIBE SPARKOL EFEKTIF MENINGKATKAN PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG ASI EKSKLUSIF - Yayu Sri Indra Arianto; Linda Suwarni; Abrori Abrori (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2021)
Background: Exclusive breastfeeding is one of the important factors in child’s growth and development. The successful exclusive breastfeeding influenced by knowledge and attitudes of mother regarding this issue. Both of these must be improved since the beginning of pregnancy. Increased knowledge and attitudes can be pursued through health promotion using media. This research aims to determine the effect of a media named Sparkol Video Scribe on increasing knowledge and attitudes of pregnant women regarding exclusive breastfeeding in the working area of Puskesmas Sanggau. Method: The design of this research uses a quasi-experimental design with one group pretest-posttest design without a control group. An amount of a sample is 36 pregnant women. Data collected through non-stimulating interviews using a questionnaire instrument. Processing of the data using computer statistic application. Data analyzed by Wilcoxon Signed Rank Test. Results: The results obtained, there are differences in the knowledge and attitudes of pregnant women about exclusive breastfeeding before and after treatment with p-value=0,00 (<0,05). Conclusion: It can be concluded that the use of Sparkol Video Scribe has an effect on increasing the knowledge and attitude of pregnant women regarding exclusive breastfeeding in the working area of Puskesmas Sanggau. It is recommended to Puskesmas Sanggau to innovate using Sparkol Video Scribe in carrying out other health promotions to the community in its territory.